ANALISIS TENTANG MANFAAT KEIKUTSERTAAN MAHASISWA DALAM ORGANISASI KEMAHASISWAAN (STUDI PENGURUS BEM UR PERIODE 2014-2015) - Erlinda, Sri; ', Walimah; ', Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was motivated by the influence of student organizations in shaping the character of the students as candidates for the carrier changes. So the student organization is considered appropriate measures to strengthen the soft skills and hard skills of the students to prepare lunch later in the day. Therefore, the authors take the title of the study "Analysis of the benefits of student involvement in Student Organizations (BEM UR Management Study Period 2014-2015)". The aim of this study to determine the benefits of student participation in student organizations. The study population was BEM UR period 2014-2015 amounting to 104 people and a sample of this research amount to 52 people. Data collection instruments questionnaire consisting of 19 statements and interviews consisted of 19 questions. In the analysis of the data, the author uses qualitative descriptive analysis.The results of this study indicate that the UR BEM 2014-2015 period, which can benefit from participating in the organization of visits of students of 52 percent as much as 92.20% of respondents answered yes. The advantages of the most commonly observed by BEM UR No 4 of 19 other advantages, namely on the one hand cooperate to obtain benefits in the form of multi-disciplinary working group (100%). The second advantage to have a responsible attitude (100%).Thirdly, expanding the advantage to improve (100%) and fourth advantage of the possibility of critical (100%). As a reference to the opinion (Husaini Usman Ali Hamsah) then the hypothesis can be accepted.   Key Words: Student Organizations, BEM UR